Plant dehydrins and dehydrin-like proteins: characterization and participation in abiotic stress response - Szlachtowska, Zofia; Rurek, Michał (Frontiers in Plant Science, 2023)
Abiotic stress has a significant impact on plant growth and development. It causes changes in the subcellular organelles, which, due to their stress sensitivity, can be affected. Cellular components involved in the abiotic stress response include dehydrins, widely distributed proteins forming a class II of late embryogenesis abundant protein family with characteristic properties including the presence of evolutionarily conserved sequence motifs (including lysine-rich K-segment, N-terminal Y-segment, and often phosphorylated S motif) as well as high hydrophilicity and disordered structure in the unbound state. Selected dehydrins and few poorly characterized dehydrin-like proteins participate in cellular stress acclimation and are also shown to interact with organelles. Through their functioning in stabilizing biological membranes and binding reactive oxygen species, dehydrins and dehydrin-like proteins contribute to the protection of fragile organellar structures under adverse conditions. Our review characterizes participation of plant dehydrins and dehydrin-like proteins (including some organellar proteins) in plant acclimation to diverse abiotic stress conditions and summarizes recent updates on their structure (the identification of dehydrin less conserved motifs), classification (new proposed subclasses), tissue- and developmentally-specific accumulation as well as key cellular activities (including also organellar protection under stress acclimation). Recent findings on the subcellular localization (with the emphasis on mitochondria and plastids) and prospective applications of dehydrins and dehydrin-like proteins in functional studies to alleviate the harmful stress consequences by means of plant genetic engineering and genome editing strategy are also discussed.